Radio resource management for single and two-hop device-two-device communications - Silva Júnior, José Mairton Barros da (2014)
The increasing demand for fast multimedia services and the scarcity of electromagnetic spectrum has motivated the research of technologies able to increase the capacity of wireless systems without requiring additional spectrum. In this context, Device-to-Device (D2D) communication represents a promising technology. By enabling direct and low-power communication among devices, D2D communication leads to an increased and intelligent spatial reuse of radio resources allowing to offload the data transport network. As a result, the overall system capacity and specially the spectral efficiency is increased; and the proximity between devices allows data transfer with low delays and high rates without requiring extra power from devices’ batteries. However, in order to realize the potential gains of D2D communications as a secondary network of the cellular (primary) one, some key issues must be tackled. Assuming that the communicating devices are aware of each other, the actual link (channel) conditions must be evaluated. If beneficial, Radio Resource Management (RRM) techniques would be employed so that the co-channel interference caused in cellular devices would be mitigated. Such techniques may be summarized as: grouping, mode selection, and power control. In this thesis, I focus my attention on the RRM for D2D communications underlaying a Long Term Evolution (LTE)-like network, and the main RRM techniques to mitigate the co-channel interference. Aiming at the reduction of the intra-cell interference and at the improvement of spectral efficiency, I formulate a joint grouping and power allocation problem. However, due to its complexity I propose suboptimal methods to group cellular and D2D User Equipments (UEs) with the goal of minimizing intra-cell interference, taking into account spatial orthogonality between the UEs that share the same resources. In addition, I analyze methods to decide if D2D-capable UEs should communicate directly to one another or in the conventional way via the Evolved Node B (eNB). The results show that D2D communications can improve the spectral efficiency of the system and that most of this improvement can be achieved by suitably grouping the UEs for sharing resources based on successive orthogonal projections and matching different spatial compatibility metrics. Moreover, in this thesis I argue that D2D technology can be used to further increase the spectral and energy efficiency if the key D2D RRM algorithms are suitably extended to support network assisted multi-hop D2D communications. Specifically I propose a novel, distributed utility maximizing power control (PC) scheme that is able to balance spectral and energy efficiency while taking into account mode selection and resource allocation constraints that are important in the integrated cellular-D2D environment. The analysis and numerical results indicate that multi-hop D2D communications combined with the proposed PC scheme can be useful not only for harvesting the potential gains previously identified in the literature, but also for extending the coverage of cellular networks